Management of Iatrogenic Rupture of Profunda Femoris Artery after Femoral Fracture Fixation with Stent Graft Implantation - Varastehravan, Hamidreza (Tehran University of Medical Sciences, 2010)
Vascular injuries with acute or chronic arterial hemorrhage after femoral shaft fractures are a rare but a life-threatening complication. We observed a case of iatrogenic rupture of the profunda femoris artery after the internal fixation of a femoral shaft fracture. The pseudoaneurysm, presenting with painful expansile swelling and hemodynamic instability, together with the rupture was evident on femoral angiography. Endovascular stent graft placement was performed successfully, and there was no sign or symptom at 9 months’ follow-up.